Implementation of Digital Parenting in Grade VI Children of SD Ibrahimy 1 Sukorejo in the Salafiyah Syafi'iyah Islamic Boarding School - Ilham Akbar; Noradinah Jaidi (Sekolah Tinggi Ilmu Al-Qur'an (SIQ) Amuntai Kalimantan Selatan, 2026)
This study analyzes the implementation of digital parenting among parents of sixth-grade students at SD Ibrahimy 1 Sukorejo, situated within the pesantren-based educational environment. The rapid development of digital technology requires adjustments in parenting practices, particularly in supervising gadget use, strengthening digital literacy, and fostering children's religious character. Employing a descriptive qualitative approach, this research collected data through in-depth interviews, direct observations, and documentation analysis to obtain a comprehensive understanding of digital parenting practices in a pesantren-oriented school setting. The findings reveal that digital parenting is implemented through regulatory and collaborative approaches, in which parents impose time limits, monitor children's online activities, and direct them toward educational and religious content. Nevertheless, several challenges persist, including limited parental digital literacy, unequal access to digital devices, and tensions between modern technological demands and the pesantren culture that tends to be cautious toward gadget use. The study concludes that effective digital parenting requires sustained synergy among schools, parents, and the pesantren environment through the reinforcement of religious values, gradual digital literacy development, and consistent guidance in children's digital activities.